Analisis Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Belanja Modal Pada Pemerintah Daerah Kabupaten/Kota Provinsi Jawa Timur 2019-2021 - Dian Tri Agustin; Gideon Setyo Budiwitjaksono (Ekonomis: Journal of Economics and Business, 2022)
The purpose of this study was to determine the effect of Regional Original Income, General Allocation Funds, and Special Allocation Funds on Capital Expenditures of the Regency/City Government of East Java Province 2019-2021. This research data uses secondary data obtained through the official website of the Ministry of Finance DJPK. The sample selection technique used in this study was purposive sampling. The number of samples in this study was 102 samples. Based on the results of research that has been carried out, Regional Original Income and General Allocation Funds have an effect on Capital Expenditures. Meanwhile, the Special Allocation Fund has no effect on Capital Expenditures.